The Relationship between Body Composition with Blood Pressure and Sleep Quality in Male Dormitory Student at Allameh Tabataba'i University - Mehdi Kushkestani; Mohsen Parvani; Shiva Ebrahimpour Nosrani; Seyed Yousef Bathaeezadeh (New Approaches in Sport Sciences, 2019)
Background and Pupose: Hypertension and poor sleep quality can increase the risk of cardiovascular diseases, diabetes, stroke, etc. Therefore, the purpose of this study was to investigate the relationship between body compositions with hypertension and sleep quality in male students living in Allameh Tabataba'i University dormitory. Material and Method: The present study was descriptive-correlational. The statistical population consisted of 170 male dormitory students of Allameh Tabataba'i University who were randomly selected. First, body composition indices and blood pressure of subjects were measured and recorded. Then, the Pittsburgh Questionnaire were completed by students (PSQI) to assess their sleep quality. Data were analyzed using SPSS 21 software at a significant level (P